2009
DOI: 10.1007/s10549-009-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of birthplace on breast cancer diagnosis and treatment for Hispanic women

Abstract: Research has shown that Hispanic women in the United States are diagnosed with breast cancer at more advanced stages and initiate treatment later than non-Hispanic white women. We investigated whether stage at breast cancer diagnosis and receipt of primary therapy differ by ethnicity and birthplace among US-born Hispanic, foreign-born Hispanic, and white women. We studied 31,012 Hispanic women and 372,313 white women with a first diagnosis of invasive breast cancer during 1988 and 2005 living in a SEER area. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 55 publications
(61 reference statements)
4
23
0
Order By: Relevance
“…Social and cultural barriers, like “fear to be left by her partner, poor awareness of the population and primary health providers, as well as deficient mammographic screening programs,” could lead to an advanced stage at diagnosis 4. Hispanic women have been found to have a 1.7- to 2.5-fold elevation in the risk of stages III and IV tumors, compared to non-Hispanic whites 26,14. Warner et al3 found Hispanic and other minority women were more likely to show up with cancer symptoms versus a problem detected through screening mammography, and experienced longer times from initial signs of cancer to final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Social and cultural barriers, like “fear to be left by her partner, poor awareness of the population and primary health providers, as well as deficient mammographic screening programs,” could lead to an advanced stage at diagnosis 4. Hispanic women have been found to have a 1.7- to 2.5-fold elevation in the risk of stages III and IV tumors, compared to non-Hispanic whites 26,14. Warner et al3 found Hispanic and other minority women were more likely to show up with cancer symptoms versus a problem detected through screening mammography, and experienced longer times from initial signs of cancer to final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced access to healthcare among foreign-born Hispanic women may result in greater time delay between the date of cancer diagnosis and the date of treatment, as well as the quality of treatment and post-treatment follow-up [45]. While a detailed exploration of potential treatment differences between U.S.- and foreign-born Hispanics is beyond the scope of this manuscript, nativity disparities in cancer treatment have been documented for breast, lung, and colorectal cancer [46, 47], and may exist for cervical cancer. We also cannot rule out other explanations (e.g., characteristics related to human papillomavirus infection) as we rely on variables available in SEER.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown disparities among US and immigrant populations in cancer information, 4 screening rates, 510 early diagnosis, 11 quality of care, 12 receipt of recommended treatment, 11,12 and survival outcomes. 13 Identified barriers to access health services include access to care factors (e.g.…”
Section: Introductionmentioning
confidence: 99%